Find 3x - y - 3z if x = -2, y = 1, and z = -2.

If x = -2, y = 1, and z = -2 , 3x - y - 3z = -1. 3x - y - 3z = 3*(-2) - 1 - 3*(-2) = -6 - 1 + 6 = - 7+ 6 = -1

Question

Asked 11/18/2010 1:15:31 PM

Updated 9/15/2014 7:34:27 AM

1 Answer/Comment

Edited by andrewpallarca [9/15/2014 7:34:27 AM]

s

Rating

8

If x = -2, y = 1, and z = -2 , 3x - y - 3z = -1.

3x - y - 3z

= 3*(-2) - 1 - 3*(-2)

= -6 - 1 + 6

= - 7+ 6

= -1

3x - y - 3z

= 3*(-2) - 1 - 3*(-2)

= -6 - 1 + 6

= - 7+ 6

= -1

Added 9/15/2014 7:32:00 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/15/2014 7:34:29 AM], Rated good by andrewpallarca

3x - y - 3z if x = -2, y = 1, and z = -2. **Weegy:** (3x-2) squared is 9x^2 - 12x + 4. (More)

Question

Not Answered

Updated 8/10/2014 3:51:03 PM

1 Answer/Comment

3x - y - 3z, x = -2, y = 1, and z = -2:

3(-2) - 1 - 3(-2)

= -6 - 1 + 6

= -6 + 5

= -1

3(-2) - 1 - 3(-2)

= -6 - 1 + 6

= -6 + 5

= -1

Added 8/10/2014 3:51:01 PM

This answer has been confirmed as correct and helpful.

34,448,781

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 612 [Total 6485] Ratings 11 Comments 502 Invitations 0 Offline

There are no comments.